Diversion as an Instrument to Terminate Criminal Investigations Conducted by Children Through the Issuance of SP3 by Investigators - Benito Harleandra; Eva Achjani Zulfa; Iza Fadri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This research is the result of research on diversion as an instrument for stopping criminal investigations through the issuance of SP3 by investigators against Children in Conflict with the Law (AKH) at the investigation stage. This research was conducted using qualitative descriptive research methods and analytical descriptive methods, namely research methods by describing data collected through library research, where researchers studied and took data from various literatures in the form of books, official reports, scientific journals, articles, and news. The results of the study show, firstly, if the diversification is successful and the results of the diversion agreement are stated, based on the decision of the District Court, the Investigator in this case the South Jakarta Metro Police issues an Investigation Termination Order (SP3) after the diversion agreement is fully implemented. Second, Article 109 paragraph (2) of the Criminal Procedure Code has limitedly stated the reasons that can be used by investigators as the basis for stopping an investigation, namely: (i) there is not enough evidence; (ii) the incident turned out to be not a criminal act; or (iii) the investigation is terminated by law. As such, diversion has no relevance to the termination of the investigation or diversion cannot be used as a reason to stop the investigation. Because diversion with the termination of the investigation is a different matter, both in terms of the reasons that form the basis for its implementation and the process.